2015
DOI: 10.1093/dnares/dsv012
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive, genome-wide analysis of autophagy-related genes identified in tobacco suggests a central role of autophagy in plant response to various environmental cues

Abstract: Autophagy is an evolutionarily conserved mechanism in both animals and plants, which has been shown to be involved in various essential developmental processes in plants. Nicotiana tabacum is considered to be an ideal model plant and has been widely used for the study of the roles of autophagy in the processes of plant development and in the response to various stresses. However, only a few autophagy-related genes (ATGs) have been identified in tobacco up to now. Here, we identified 30 ATGs belonging to 16 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 50 publications
6
72
0
Order By: Relevance
“…The quantity of ATGs in sweet orange is similar to the quantity in grape (35 VvATGs) [13], banana (32 MaATGs) [12], rice (33 OsATGs) [7], and foxtail millet (37 SiATGs) [11], suggesting very conservative evolution of ATGs in these plants. Among the 19 core CsATGs, we found that CsATG1, CsATG8, and CsATG18 contained multiple members, which is similar to that in Arabidopsis and other plants [1,8,13]. However, unlike having two ATG4, ATG12, and ATG13 genes and one VTI12 in Arabidopsis, sweet orange has one member of CsATG4, CsATG12, and CsATG13 and four members of CsVTI12.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The quantity of ATGs in sweet orange is similar to the quantity in grape (35 VvATGs) [13], banana (32 MaATGs) [12], rice (33 OsATGs) [7], and foxtail millet (37 SiATGs) [11], suggesting very conservative evolution of ATGs in these plants. Among the 19 core CsATGs, we found that CsATG1, CsATG8, and CsATG18 contained multiple members, which is similar to that in Arabidopsis and other plants [1,8,13]. However, unlike having two ATG4, ATG12, and ATG13 genes and one VTI12 in Arabidopsis, sweet orange has one member of CsATG4, CsATG12, and CsATG13 and four members of CsVTI12.…”
Section: Discussionmentioning
confidence: 50%
“…However, unlike having two ATG4, ATG12, and ATG13 genes and one VTI12 in Arabidopsis, sweet orange has one member of CsATG4, CsATG12, and CsATG13 and four members of CsVTI12. This indicates a citrus crop-specificity in the number of these ATGs [1,8]. On the basis of gene duplication analysis, a high proportion of segmental duplications was predicted for those multiple members of CsATGs, especially for CsATG8.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…By contrast, the expression levels of some ATG s are low, such as in flowers, shoot apex and roots, possibly due to their different functional specificity in various types of plant tissues and cells. Similarly, in Nicotiana tabacum , the expression levels of some NtATG s are also particularly high in pollen and anthers (Zhou et al , ). These data may suggest potential regulatory roles of autophagy in proper development and/or functions of male gametes.…”
Section: Autophagy‐related Proteins In Plant Reproductionmentioning
confidence: 96%
“…Thus far, over 30 ATG s have been identified in Arabidopsis , rice, tobacco, and pepper based on comprehensive, genome-wide analysis (Xia et al, 2011; Zhou et al, 2015; Zhai et al, 2016). ATGs can be divided into three categories with respect to their function: (i) ATG1-ATG13 comprising the kinase complex, an upstream regulator that initiates autophagosome formation (Suttangkakul et al, 2011); (ii) The ATG9 and ATG6/vps30 complexes involved in vacuolar protein sorting in which ATG9 interacts with ATG2 and ATG18, boosting phagophore expansion.…”
Section: The Autophagy-related Genes (Atgs) Involved In Abiotic Stresmentioning
confidence: 99%